2011
DOI: 10.1111/j.1365-2834.2010.01180.x
|View full text |Cite
|
Sign up to set email alerts
|

Relations among depression, self-efficacy and optimism in a sample of nurses in Taiwan

Abstract: The results of the present study indicate that there is an immediate need to pay further attention to nurses' depression issues. It is therefore suggested that Nursing Managers take an empowering approach to strengthen nurses' self-efficacy and optimism levels to prevent depression in this profession.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 53 publications
2
51
0
1
Order By: Relevance
“…A large body of evidence shows that concept of self efficacy has a general role on mental health [21][22][23]. Tahmassian and colleagues reported that there is a significant and negative relationship between self-efficacy and depression ( = −0.42) and anxiety ( = −0.46) [24].…”
Section: Hospital Anxiety and Depression Scale (Hads)mentioning
confidence: 99%
“…A large body of evidence shows that concept of self efficacy has a general role on mental health [21][22][23]. Tahmassian and colleagues reported that there is a significant and negative relationship between self-efficacy and depression ( = −0.42) and anxiety ( = −0.46) [24].…”
Section: Hospital Anxiety and Depression Scale (Hads)mentioning
confidence: 99%
“…Increased psychological capital, especially resilience among nurses, is important because resilient nurses are less likely to have job stress and burnout, have better health, have higher levels of job engagement and intention to stay in the organization (24)(25)(26). Also, the amount of optimism and selfefficacy are related to lower level of depression among nurses, and psychological capitals (hope, optimism, resilience, and self-efficacy) are generally related to nurses' commitment to hospital missions (27).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature review of Koinis and his colleagues (2014), it is being accented that the working conditions of the health professionals, working hours, disturbed or minimum communication with co-workers and lack of sleep can contribute to the development of psychiatric symptoms and long-term to depression. In the current bibliography, the rates of depression symptoms in health care professionals differ importantly, depending on the methodology followed every time as well as the country where the research is conducted (for instance : Abbas et al 2013;Gao et al 2011;Chang et al 2010). …”
Section: Depression and Hhealthcare Providersmentioning
confidence: 99%
“…For instance, it has been investigated in nurses (Chang et al 2010), nursing technicians and nursing assistants (Rios et al 2010), physicians (Levine and Bryant 2000), social workers (Siebert 2004), and intellectual disability support staff (Mutkins et al 2011). In the literature review of Koinis and his colleagues (2014), it is being accented that the working conditions of the health professionals, working hours, disturbed or minimum communication with co-workers and lack of sleep can contribute to the development of psychiatric symptoms and long-term to depression.…”
Section: Depression and Hhealthcare Providersmentioning
confidence: 99%
See 1 more Smart Citation